Indonesian-English Code Mixing on Maudy Ayunda's Podcast: "3 Hal Penting untuk Meraih Kesuksesan" - Putri, Febiola Anggita; Laila, Malikatul; Mujazin, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study investigates the patterns of code mixing used in Maudy Ayunda's podcast entitled "3 Hal Penting untuk Meraih Kesuksesan". This study aims primarily to specify the type of code mixing and analyse the reason of code mixing employed by the speakers in the video.Methodology: This study employed qualitative method. This study also utilized Muysken's (2000) theory to determine the classifications of code mixing and Hoffman's (1991) theory to analyse the reasons of code mixing used in podcast. The researcher made a transcript of the research subject, then analysed and grouped the obtained utterances from the types of code mixing in accordance with the theory used.Results: This study discovered 402 utterances in total and inferred that three kinds of code mixing by Muysken exist in the video. First, insertion is discovered 305 cases. Second, alternation is 71 cases. Last, there are 26 cases of data congruent lexicalization. Furthermore, the seven types reason of code mixing by Hoffman is also discovered by talking about a particular topic being commonly found in 328 cases. Quoting somebody else is 3 cases, be emphatic is 41 cases, interjection is 3 cases, repetition used for clarification is 8 cases, Intention of clarifying the speech content for the interlocutor is 8 cases, and expression of a group identity is 10 cases.Applications/Originality/Value: This study provides insights code mixing used to bond closeness, enhance message clarity, and convey group identity